(untitled) (Acta Scientiarum. Health Sciences, 2024)
The activities developed by Community Health Agents are strategic for child growth and development due to the uniqueness and proximity with which these actors perform their interventions in the community. Such actions favor children’s health, resulting in a reduction in child mortality, improvement in growth deficit and malnutrition, and an increase in vaccination coverage and breastfeeding. The objective of the study was to know the perception of community health agents about child growth and development. This is an exploratory descriptive, qualitative study, carried out with 30 Community Health Agents who worked in Primary Care and Family Health Strategy Teams in a municipality in the central region of Rio Grande do Sul, Brazil. Data were collected from April to July 2021, through an online questionnaire and analyzed according to Discursive Textual Analysis. Data analysis allowed the construction of four categories, namely: Growth as a process of physical evolution of children; Child development as a broad process of evolution; Elements that facilitate the work of Community Health Agents; and Elements that hinder the work of Community Health Agents. For the study participants, children growth is associated with the physical evolution of children, while child development is understood as a broader process that is influenced by the environment and the external conditions in which children live. The Community Health Agents have a strategic and unique professional role in the monitoring of these processes, as they are capable of identifying diseases that need specific attention and providing care in a timely manner.